Morphological profile of different types of top young female European basketball players - Erculj, F.; Bracic, M. (Collegium Antropologicum, 2014)
Basketball is a team sport involving several types of players who differ in terms of body height and other morphological dimensions. This study aimed to establish and analyze the morphological characteristics of top young female European basketball players, the development levels of the morphological characteristics of three basic types of such players and any differences among them. The sample of subjects comprised 115 female basketball players aged 14.64 (±0.48) years. They were divided into three groups according to their playing position: guard (N=51), forward (N=33) and center (N=31). The study applied 23 morphological measures, based on which the somatotype components, percentages of bone, muscle and fat tissue and other morphological indexes were calculated. Statistically significant differences (p< 0.05) were established between individual types of players in terms of their body height, body mass and the three somatotype components, by using a one-way analysis of variance, whereas no such differences were identified in terms of their bone, muscle and fat tissue percentages. There were no differences even after the effect of body height was eliminated by using a multivariate analysis of covariance. The effect of the covariate was only statistically significant in terms of bone tissue percentage. The results of the study thus refute the assumption that it is possible to differentiate player types according to their proportions of fat and muscle tissue.